Biological Characteristics and Genomic Analysis of Acinetobacter nosocomialis Lytic Phage XC1 - Chuhan Wang; Shuchuan Zhao; Hailin Jiang; Hongyan Shi; Jinghua Li; Chunyan Zhao; Honglan Huang (Current Issues in Molecular Biology)
This study aims to isolate and characterize the lytic phage XC1 targeting Acinetobacter nosocomialis and systematically analyze its biological properties and genomic structure, providing theoretical support for developing novel treatments against antibiotic-resistant infections. Phage XC1 was isolated and purified from lake water. Its morphology, optimal multiplicity of infection (MOI), thermal stability, and pH tolerance were analyzed. Genomic sequencing and functional annotation were performed to identify its lysis-associated genes. Phage XC1 demonstrated a short latent period (20 min) and high burst size (310 plaque-forming units per cell, PFU/cell). It remained stable under temperatures of 50–60 °C and at pH 7, indicating good environmental stability. Genomic analysis revealed a 45,324 bp genome with a GC content of 38.21%, including 84 open reading frames (ORFs), without any lysogenic, virulence, or antibiotic-resistance genes, confirming its safety. Average Nucleotide Identity (ANI) analysis shows that the ANI values between phage XC1 and other phages range from 80% to 95%. As the ANI value between strains of the same species is typically ≥95%, this suggests that phage XC1 may be a previously undiscovered new phage. Classified within the genus Obolenskvirus (class Caudoviricetes), phage XC1 is a virulent bacteriophage with rapid lytic activity and extreme environmental tolerance. Its therapeutic potential against multidrug-resistant infections, either as a monotherapy or in synergy with antibiotics, warrants further investigation.